77 Long-term Valbenazine Treatment in Patients with Schizophrenia/Schizoaffective Disorder or Mood Disorder and Tardive Dyskinesia. (12th March 2019) - Lindenmayer, Jean-Pierre; Marder, Stephen R.; Singer, Carlos; Comella, Cynthia; Farahmand, Khody; Burke, Joshua; Jimenez, Roland; Siegert, Scott
Abstract: Background: Patients treated with antipsychotics, regardless of psychiatric diagnosis, are at risk for developing tardive dyskinesia (TD), a potentially debilitating drug-induced movement disorder. Valbenazine (INGREZZA; VBZ) is a novel vesicular monoamine transporter 2 (VMAT2) inhibitor approved to treat TD in adults. Data from KINECT 4 (NCT02405091) were analyzed to evaluate the long-term effects of VBZ in adults with schizophrenia/schizoaffective disorder (SZD) or mood disorder (MD) and moderate or severe TD. Methods: KINECT 4 included open-label treatment (48weeks) followed by washout (4weeks). Entry requirements included: moderate or severe TD, qualitatively assessed at screening by a blinded, external reviewer; DSM diagnosis of SZD or MD; psychiatric stability (Brief Psychiatric Rating Scale score <50). Stable concomitant psychiatric medications were allowed. Dosing was initiated at 40mg, with escalation to 80mg at Wk4 if participants had a Clinical Global Impression of Change-TD score of ≥3 (minimally improved to very much worse) and tolerated 40mg. A reduction to 40mg was allowed if 80mg was not tolerated (80/40mg); participants unable to tolerate 40mg were discontinued. Safety was the primary focus, but the Abnormal Involuntary Movement Scale (AIMS) total score (sum of items 1–7) was used to evaluate changes in TD. Mean changes from baseline (BL) in AIMS total score (rated by on-site investigators) were analyzed descriptively. Safety assessments included treatment-emergent adverse events (TEAEs) and psychiatric scales (Positive and Negative Syndrome Scale [PANSS], Calgary Depression Scale for Schizophrenia [CDSS], Montgomery-Åsberg Depression Rating Scale [MADRS], Young Mania Rating Scale [YMRS], and Columbia-Suicide Severity Rating Scale [C SSRS]). Results: Of 163 participants in the analyses, 103 completed the study. Adverse events (n=26) was the most common reason for discontinuation. Analyses included 119 participants with SZD (40mg=37; 80mg=76; 80/40mg=6) and 44 with MD (40mg=8; 80mg=31; 80/40mg=5). At Wk48, mean improvements from BL in AIMS total score were: SZD (40mg, –10.1; 80mg, –10.7); MD (40mg, 10.2; 80mg: –11.6). AIMS total scores at Wk52 (end of washout) indicated a return toward BL levels. Compared to SZD, the MD subgroup had a higher incidence of any TEAE (84% vs 61% [all doses]) but fewer TEAEs leading to discontinuation (7% vs 18%). Urinary tract infection was the most common TEAE in the MD subgroup (18%); somnolence and headache were most common in the SZD subgroup (7% each). Psychiatric status remained stable from BL to Wk48: SZD (PANSS positive, –0.7, PANSS negative, –0.6; CDSS, –0.7); MD (MADRS, –0.3; YMRS, –0.3). Most participants (95%) had no change in C-SSRS score during the study. Conclusion: Sustained and clinically meaningful TD improvements were observed with VBZ, regardless of primary psychiatric diagnosis. VBZ was generally well tolerated and no notable changes in psychiatric status were observed. Funding Acknowledgements: Supported by Neurocrine Biosciences, Inc.